2018
DOI: 10.1007/978-981-10-6181-3
|View full text |Cite
|
Sign up to set email alerts
|

The Nature of Variation in Tone Sandhi Patterns of Shanghai and Wuxi Wu

Abstract: The primary goal of this dissertation is to understand the variation patterns in suprasegmental processes and what factors influence the patterns. To answer the questions, we investigated the variation patterns of tone sandhi in the Shanghai and Wuxi Wu dialects of Chinese.Shanghai disyllables and trisyllables have been documented to have two different sandhi patterns: tonal extension and tonal reduction. Some items can only undergo tonal extension, some items can only undergo tonal reduction, and some can var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
2

Year Published

2021
2021
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 92 publications
2
10
2
Order By: Relevance
“…For example, when /tsʰɔ24 vɛ13/ 'to fry + rice' means 'fried rice' as a compound noun, it can only undergo extension sandhi [tsʰɔ33 vɛ44]; when it means 'to fry rice' as a verb phrase, it can undergo extension sandhi or tonal reduction [tsʰɔ44 vɛ13]. Yan (2018) further investigated the factors that influence the variation pattern of disyllabic tone sandhi in Shanghai. The study reported a goodness rating experiment for the variant forms with native Shanghai speakers in tandem with semantic transparency and subjective frequency ratings from the same speakers.…”
Section: Rightward Tonal Extensionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, when /tsʰɔ24 vɛ13/ 'to fry + rice' means 'fried rice' as a compound noun, it can only undergo extension sandhi [tsʰɔ33 vɛ44]; when it means 'to fry rice' as a verb phrase, it can undergo extension sandhi or tonal reduction [tsʰɔ44 vɛ13]. Yan (2018) further investigated the factors that influence the variation pattern of disyllabic tone sandhi in Shanghai. The study reported a goodness rating experiment for the variant forms with native Shanghai speakers in tandem with semantic transparency and subjective frequency ratings from the same speakers.…”
Section: Rightward Tonal Extensionmentioning
confidence: 99%
“…Shanghai tone sandhi has been reported to have two different patterns-tonal extension or tonal reduction-depending on the properties of syntactic structure, semantic transparency, and usage frequency: Some lexical items can only undergo tonal extension, some can only undergo tonal reduction, and some can have both forms (Xu, Tang, & Qian, 1981, 1982Yan, 2018). Not only will the phonological alternation, in this case, tone sandhi, lead to a mismatch between surface and stored representations (Chien, Sereno, & Zhang, 2016;Nixon, Chen, & Schiller, 2015), but the variation pattern may also make the recognition process more challenging.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas rightdominant sandhi applies to loosely connected words or phrases (verb-object, subject-verb, verb-modifier, and coordinated structures). For example, when 头痛 means "headache" as a compound, left-dominant sandhi is applied; when it means "(my) head aches" as a subject-predicate phrase, right-dominant sandhi is applied (Yan, 2016).…”
Section: Bi-directional Tone Sandhi Systemsmentioning
confidence: 99%
“…Participants in the Shanghai experiment also provided production data for real and novel disyllabic words, but the novel disyllables were cued as modifier-noun combinations (M-Ns) instead of V-Ns, as V-Ns are generally phrases in Shanghai and do not participate in tone sandhi [5] [40]. All tonal combinations were tested in [39], but we only focus on the combinations between 51 and the two tones on nonchecked syllables with a voiceless onset (51,35) due to space limitation.…”
Section: Shanghaimentioning
confidence: 99%
“…The same methods were used to elicit the production of both real and novel words in Wuxi, but the novel words included both M-N and V-N items, as no clear difference in sandhi production between the two has been documented (but see [40]). Twenty native speakers with a mean age of 27 participated in the experiment in Wuxi.…”
Section: Wuximentioning
confidence: 99%